2020
DOI: 10.1108/ijph-03-2020-0019
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive dysfunction in older prisoners in Germany: a cross-sectional pilot study

Abstract: Purpose The purpose of this study is to collect the first empirical data on the cognitive state of elderly prisoners in Germany and to examine associations between cognitive function and sociodemographic, clinical and incarceration characteristics. Design/methodology/approach All prisoners aged 60 years and older of five prisons in North Rhine-Westphalia, Germany, were asked to participate. The cognitive screening instruments mini-mental state examination (MMSE) and the DemTect were used to assess global cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Our finding of an increased risk of dementia and MCI in those older adults with criminal background is in line with recent studies showing a more marked cognitive impairment in older prisoners in comparison to older adults in the community [21][22][23] ; even thought these studies are scarce and have small sample sizes. The strength of the association between criminal background and dementia are comparable to the relative risks previously reported for known dementia risk factors (OR range from 1.46 to 1.96), such as depression, anxiety 14 , midlife hypertension, diabetes mellitus or low education 13 .…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of an increased risk of dementia and MCI in those older adults with criminal background is in line with recent studies showing a more marked cognitive impairment in older prisoners in comparison to older adults in the community [21][22][23] ; even thought these studies are scarce and have small sample sizes. The strength of the association between criminal background and dementia are comparable to the relative risks previously reported for known dementia risk factors (OR range from 1.46 to 1.96), such as depression, anxiety 14 , midlife hypertension, diabetes mellitus or low education 13 .…”
Section: Discussionsupporting
confidence: 92%
“…A systematic review by Brooks et al (2018) on MCI and dementia in older prisoners came to the conclusion that the prevalence rates are underreported and that there is lack of cognitive screening routines. Notably, a recent cross-sectional study by Verhülsdonk et al ( 2020 ) including N = 58 German prisoners reported that more than 40% of the study participants were classified as cognitively impaired. Age is beyond debate the most important risk factor for cognitive decline.…”
Section: Introductionmentioning
confidence: 97%
“…Other studies mention figures of around 40% for cognitive deterioration, with a significant association between cognitive performance and age, educational attainment, duration of current sentence and depressive symptoms. Furthermore, almost half presented deficits in executive functioning 35 . Low cognitive performance was correlated with more visits to A&E and hospital admissions 36 , and an association was also found between diagnoses of dementia and convictions for sexual crimes 32 .…”
Section: Resultsmentioning
confidence: 99%